P-151 The value of a night service for hospice-at-home: reasons for making contact at night. Issue Volume 8: Issue (2018)Supplement 2 (November 2018) - Clarke, Jo; Varvel, Sue
Abstract : Background: People approaching the end of their lives have physical and psychological needs that should be met in a timely way, at any point during the night or day, and met in a way which addresses their needs and preferences. Crises at any time require prompt, safe and effective urgent care (NICE 2011). Methods: Rennie Grove Hospice Care (RGHC) provides 24/7 care, with a night service available from 9.15 pm to 7.15am. RGHC conducted an independent study to identify the value of the service, including reasons people make contact at night and how many calls could be settled without a visit. Over the study period (145 nights) each call was charted with demographic details, reason for call and outcome. Results: 550 calls were received, resulting in 335 visits. On seven nights there were no visits, the highest number in a night was nine, with an average 3.79 visits per night. Only those consenting to participate were analysed, reducing eligiblity to 351 calls and 208 visits. Of these, reasons for a night visit included symptom control (64%), carer support (19%), death (13%), death verified by night team (9%), message (7.5%), planned visit (7%) and 'other' (4%). Major symptoms included pain (42%), anxiety (32%), nausea (17%) and a small number with chest problems, bowel issues, pyrexia, syringe pumps. In 143 cases a visit was not necessary due to telephone reassurance (55%), another service being more suitable (12%), the team were too busy (8%), and 12% were handed to the next shift. Conclusions: The night team plays a vital role in 24/7 care, with 40% of calls being managed without a visit. Visits were, in the main, for symptoms or problems concerning support. Death, for a Hospice at Home service also becomes a significant issue requiring a prompt and caring response.